Crítica à contrarreforma do Ensino Médio (Lei 13.415) - Cardoso, Paulo Érico Pontes (2019)
The present research investigates the "reform" of the high school sanctioned by the government of Michel Temer's government in February 2017. The Law 13.415 is being put into practice in the Bolsonaro's current presidential government. This condition demands from the analysis a follow-up in perspective, seeking to identify the direction to which the new ideological, economic determinations of alteration of the original project point, including the tendencies toward the elitisation and militarization of education. The general objective of this essay is to analyze the “reform” of on high school system within the framework of the expansion of entrepreneurship in education and the offensive of capital. In order to investigate the object in its movement, we resorted to the scientific method that explains natural, social and mental phenomena based on the study of matter in its historical modifications and contradictions, a method that allows us to understand the relation between the singularities of the singularities of the imposition of this high school “reform” and the particularities of the moment in which the process of the "reform" of the Brazilian State, inserted in a whole that is the contemporary capitalism is passing. The research is a bibliographical one, taking as a reference classic and also contemporary authors such as Marx (1983, 1993), Mészáros (2005), Saviani (1994, 1999), and of documentary nature, based on the study of the contributions legal reforms regarding the "reform" of high school system. In particular, the theoretical contributions of Kuenzer (1989) on the historical duality high school system education will be used critically; of Machado e Rocha (2017), about the counterreformation in Brazilian education and the scientific knowledge in the berlinda; de Souza Jr. (2010), on the school crisis during the regressive-destructive capital crisis; of Harvey (2014), in his critique of the madness of economic reason and of Antunes (2018), about the new proletariat of services in the digital age. The research was based on a more general analysis of the relationship between educational reforms and changes in the world of work system and the demands of the market for the training of the workers, which has undergone an education that is less propedeutic and more commodified and professionalized. The next steps of the research were to establish work and education as categorical elements for the critique of the secondary school counterreformation, to understand the influence of contemporary capitalism and its inflows on secondary education and professional education in Brazil, and, finally, the study was carried out functions, assumptions, pedagogical guidelines and curriculum of the aforementioned "reform". Both the original determinations of sanctioned legislation and the changes added by the current Ministry of Education indicates that the trend is that the "reform" accentuates the historical duality of high school system and the general lack of education of the majority of the Brazilian population.